Computer assisted reconstruction of complex proximal humerus fractures for preoperative planning - Fürnstahl, Philipp; Székely, Gábor; Gerber, Christian; Hodler, Jürg; Snedeker, Jess Gerrit; Harders, Matthias (Medical image analysis, 2012)
[Display omitted] ► Semi-automatic fracture reconstruction in two consecutive registration steps. ► Efficient contralateral matching without relying on initial fragment positions. ► Robust pairwise registration of fracture surfaces and global multipiece alignment. ► The complex planning task can be performed in a reasonable time on the GPU. Operative treatment of displaced fractures of the proximal humerus is among the most difficult problems in orthopedic shoulder surgery. An accurate preoperative assessment of fragment displacement is crucial for a successful joint restoration. We present a computer assisted approach to precisely quantify these displacements. The bone is virtually reconstructed by multi-fragment alignment. In case of largely displaced pieces, a reconstruction template based on the contralateral humerus is incorporated in the algorithm to determine the optimal assembly. Cadaver experiments were carried out to evaluate our approach. All cases could be successfully reconstructed with little user interaction, and only requiring a few minutes of processing time. On average, the reassembled bone geometries resulted in a translational displacement error of 1.3±0.4mm and a rotational error of 3.4±2.2°, respectively.